INCOME’S MODERATING ROLE IN INDONESIAN POVERTY DYNAMICS: POPULATION, HUMAN DEVELOPMENT AND UNEMPLOYMENT IN AN ISLAMIC ECONOMICS PERSPECTIVE - Asyrorroji, Muh. Jazuli (Islamic Economics Program, Faculty of Islamic Economics and Business, 2025)
This study investigates whether income moderates the effects of population size, the Human Development Index (HDI), and the open unemployment rate (OUR) on interprovincial poverty in Indonesia, and interprets the results within an Islamic economics framework emphasizing justice (‘adl) and well-being (falah). Motivated by the recurrent disconnect between poverty reduction and rising average income particularly when economic growth is not employment-intensive and access to basic services remains unequal the analysis positions income as a conditioning factor in poverty dynamics. Using panel data for 19 provinces over the period 2016–2023, the study employs fixed-effects regressions, selected on the basis of Chow and Hausman tests, and incorporates interaction terms between income and each core covariate to capture moderating effects while controlling for time-invariant provincial heterogeneity. The empirical findings indicate that population size, HDI, and OUR are significant determinants of poverty, whereas income is not statistically significant either as a direct predictor or as a moderating variable. These results suggest that increases in aggregate income alone are insufficient to modify the structural relationships linking demographic pressures, human development, labor market conditions, and poverty. From an Islamic economics perspective, effective poverty alleviation therefore requires policies that foster job-rich and inclusive growth, broaden equitable access to education and health (supporting the maqasid al-shariah of protecting life, intellect, and wealth), and reinforce labor market and social protection institutions, rather than relying solely on higher average income